THE QUALITY OF TRANS METRO PEKANBARU PUBLIC TRANSPORT BASED ON ROUTE SERVICE (STUDY CASE : ROUTE 1 AND 4B) - ABD KUDUS ZAINI; MUCHAMMAD ZAENAL MUTTAQIN (International Journal of Innovations in Engineering Research and Technology, 2021)
Public transport has become the only solution to prevent traffic jam, especially in Pekanbaru. The existence of the Trans Metro Pekanbaru really needs to be developed consistently and continuously. Each service route has its own characteristics related to the type of service and the characteristics of the route served. The purpose of this study is to determine the quality of service in each transport route so that it becomes a consideration in calculating the quality of public transportation services in the Trans Metro Pekanbaru for each of these routes. The limitation of this study is to compare only two travel routes, namely route 1 connecting Ramayana - Pandau (commercial and residential routes) and route 4B connecting the Mayor's House-BPRS Terminal (Tourist route). The results showed that there were differences in each trip route. Thus, the strategy to improve quality in terms of service time is a serious concern for Trans Metro Pekanbaru to achieve a better transportation system and towards sustainable transportation in the city of Pekanbaru.